Bhabinkamtibmas's Role in Preventing Drug Abuse in The Jurisdiction of Langsa Police Department - Muhammad Fajar Sidiq (Advances in Police Science Research Journal, 2021)
This research is based on the increasingly worrying conditions of drug abuse in Indonesia. In the jurisdiction of Langsa Police Department itself the number one crime for the last three years (2018-2020) are narcotics crime. Law enforcement and rehabilitation measures have not resolved the issue so the most effective action is preventive measures. In this case prevention efforts are carried out by community development unit and the implementation is carried out by Bhabinkamtibmas who is the spearhead of community development unit because it interacts directly with the community in the village. Therefore, research was conducted with the aim of knowing the capabilities of the Role of Bhabinkamtibmas, what efforts Bhabinkamtibmas Langsa Police Department in preventing drug abuse in the community, and what is the obstacle of Bhabinkamtibmas Langsa Police Department in preventing drug abuse in the society. This study uses management theory, prevention theory, and role theory to analyze existing problems. The focus of the research was Bhabinkamtibmas's role in preventing drug cases in the Langsa Police Department. Data collection techniques with interviews, observations and document studies. Data analysis is performed with data reduction, data serving and verification. Based on the results of the research, Bhabinkamtibmas has made several efforts such as guidance and counseling to the community and students, carrying out sideburns and visits to houses and stalls, as well as forming a pageu gampoeng Constraints found divided into two internal factors: lack of quantity and quality of personnel, inadequate budget, and less supportive infrastructure, and external factors: lack of awareness from the community , environmental factors, and pandemic factors, based on the findings the author suggested to improve the quantity and quality of personnel, secondly put Bhabinkamtibmas in the village of his target, third held infrastructure to support the performance of Bhabinkamtibmas, fourth carried out evaluation and looked for alternatives and methods in the delivery of kamtibmas message.